Impaired decision‐making and selective cortical frontal thinning in Cushing's syndrome. (1st September 2014) - Crespo, Iris; Esther, Granell‐Moreno; Santos, Alicia; Valassi, Elena; Yolanda, Vives‐Gilabert; De Juan‐Delago, Manel; Webb, Susan M.; Gómez‐Ansón, Beatriz; Resmini, Eugenia
Summary Context and objective Cushing's syndrome (CS) is caused by a glucocorticoid excess. This hypercortisolism can damage the prefrontal cortex, known to be important in decision‐making. Our aim was to evaluate decision‐making in CS and to explore cortical thickness. Subjects and methods Thirty‐five patients with CS (27 cured, eight medically treated) and thirty‐five matched controls were evaluated using Iowa gambling task (IGT) and 3 Tesla magnetic resonance imaging (MRI) to assess cortical thickness. The IGT evaluates decision‐making, including strategy and learning during the test. Cortical thickness was determined on MRI using freesurfer software tools, including a whole‐brain analysis. Results There were no differences between medically treated and cured CS patients. They presented an altered decision‐making strategy compared to controls, choosing a lower number of the safer cards (P < 0·05). They showed more difficulties than controls to learn the correct profiles of wins and losses for each card group (P < 0·05). In whole‐brain analysis, patients with CS showed decreased cortical thickness in the left superior frontal cortex, left precentral cortex, left insular cortex, left and right rostral anterior cingulate cortex, and right caudal middle frontal cortex compared to controls (P < 0·001). Conclusions Patients with CS failed to learn advantageous strategies and their behaviour was driven by short‐term reward and long‐term punishment, indicating learning problems because they did not use previous experience as a feedback factor to regulate their choices. These alterations in decision‐making and the decreased cortical thickness in frontal areas suggest that chronic hypercortisolism promotes brain changes which are not completely reversible after endocrine remission.